Angular dependent terahertz emission from the interplay between nanocrystal diamond film and plasmonic metasurface - Shuangquan Fang; Wenpeng Guo; Yuanyuan Huang; Mingjian Shi; Xuezeng Tian; Baogang Quan; Xinlong Xu; Jian Yi; Nan Jiang; Changzhi Gu (iScience, 2024)
Summary: Composite structures integrated with metasurfaces and nonlinear films have emerged as alternative candidates to enhance nonlinear response. The cooperative interaction between the two components is complicated. Herein, a split-ring resonator (SRR)-type metasurface was fabricated on a free-standing nanocrystal diamond (NCD) film utilizing electron beam lithography, electron beam evaporation, and a lift-off process. The terahertz (THz) radiation from the SRR-NCD under normal incidence originates from the high-order magnetic resonance of SRR because the NCD film cannot produce detectable THz radiation at this incident angle. As increasing the incident angle, the contribution of the THz radiation from the NCD film gradually increases until reaching 40° incident angle limitation. The results indicate that this angular-dependent THz radiation is induced by the interplay between the NCD film and SRR. This study offers a new approach to investigate nonlinear processes in composite structures.